Capture Sequencing to Explore and Map Rare Casein Variants in Goats - Rahmatalla, Siham A.; Arends, Danny; Said Ahmed, Ammar; Hassan, Lubna M. A.; Krebs, Stefan; Reissmann, Monika; Brockmann, Gudrun A. (Frontiers in Genetics, 2021)
Genetic variation in the four casein genes CSN1S1, CSN2, CSN1S2, and CSN3 have obtained substantial attention since they affect milk protein yield, milk composition, cheese processing properties, and digestibility as well as tolerance in human nutrition. Furthermore, milk protein variants are used for breed characterization, biodiversity, and phylogenetic studies. The current study aimed at the identification of casein protein variants in five domestic goats breeds from Sudan (Nubian, Desert, Nilotic, Taggar and Saanen) and three wild goat species (Capra aegagrus aegagrus (Bezoar ibex), Capra nubiana (Nubian ibex), and Capra ibex (Alpine ibex)). High-density capture sequencing of 33 goats identified in total 22 non-synonymous and 13 synonymous SNPs, of which nine non-synonymous and seven synonymous SNPs are new. In the CSN1S1 gene, the new non-synonymous SNP ss7213522403 segregated in Alpine ibex. In the CSN2 gene, the new non-synonymous SNPs ss7213522526, ss7213522558, and ss7213522487 were found exclusively in Nubian and Alpine ibex. In the CSN1S2 gene, the new non-synonymous SNPs ss7213522477, ss7213522549, and ss7213522575 were found in Nubian ibex only. In the CSN3 gene, the non-synonymous SNPs ss7213522604 and ss7213522610 were found in Alpine ibex. The identified DNA sequence variants led to the detection of nine new casein protein variants. New variants were detected for alpha S1 casein in Saanen goats (CSN1S1*C1), Bezoar ibex (CSN1S1*J), and Alpine ibex (CSN1S1*K), for beta and kappa caseins in Alpine ibex (CSN2*F and CSN3*X), and for alpha S2 casein in all domesticated and wild goats (CSN1S2*H), in Nubian and Desert goats (CSN1S2*I), or in Nubian ibex only (CSN1S2*J, CSN1S2*K). The results show that most novel SNPs and protein variants occur in the critically endangered Nubian ibex. This highlights the importance of the preservation of this endangered breed. Furthermore, we suggest validating and further characterizing the new casein protein variants.